From Touch to Literacy: Multisensory and Collaborative Pathways to Braille Readiness - Upendo Gabriel Komba; Theodora Bali; Reuben Sungwa (Universitas Nurul Jadid, 2026)
This study examined teaching strategies for developing readiness skills among Braille beginners in special pre-primary schools. Braille readiness requires tactile, motor, auditory, spatial, cognitive, and communicative foundations before literacy begins. Yet limited curricula, materials, support, and contextual evidence may weaken preparation. A qualitative phenomenographic design involved three special pre-primary schools. Data from 30 participants were collected through interviews, focus groups, and observations, then analyzed thematically. First, structured and individualized instruction strengthened tactile tracking, listening, memory, confidence, and independence. Direct teaching, additional time, questioning, repetition, and feedback supported differentiated progression. Second, multisensory and experiential activities developed tactile discrimination, concept formation, spatial awareness, and motor coordination. Real objects, songs, movement, and role-play linked experience with Braille symbols. Third, collaborative learning promoted cooperation, orientation, problem-solving, and social-emotional readiness. Its effectiveness depended on motivated teachers, materials, assistive technologies, flexible timetables, manageable class sizes, individualized support, and parental involvement. The study conceptualizes Braille readiness as an ecological capability emerging from instructional, sensory, relational, and institutional conditions. The findings inform curriculum development, teacher preparation, resource allocation, and inclusive early-literacy planning.